Petrochemical Planet Multiscalar Battles of Industrial Transformation - Mah, Alice (Duke University Press, 2023)
Drawing on research from high-level industry meetings, petrochemical plant tours, and polluted communities in the United States, China, Europe, Alice Mah examines the changing nature of the petrochemical industry as it faces the existential threats of climate change and environmental activism.